2016
DOI: 10.1002/ejoc.201600304
|View full text |Cite
|
Sign up to set email alerts
|

N‐Allenyl Amides and O‐Allenyl Ethers in Enantioselective Catalysis

Abstract: Nowadays asymmetric catalysis is an established reality in the organic synthesis community. Nevertheless, the range of applicability both in organic and in organometallic transformations is so large that seeking for new developments seems unstoppable. In this direction, from time to time a new class of "silent" organic compounds rises to prominence and creates new perspectives in the field. Allenyl amides and allenyl A personal dedication: "Asymmetric catalysis represents my personal and primary scientific con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…In continuation with our ongoing interests in the metal as well as organocatalyzed dearomatization of electron-activated arene, we have recently documented the impact of the gold counterion on the overall chemochemical, regiochemical, and stereochemical outcome of the dearomatization of C2,3-disubstituted indoles with allenamides. , …”
mentioning
confidence: 94%
“…In continuation with our ongoing interests in the metal as well as organocatalyzed dearomatization of electron-activated arene, we have recently documented the impact of the gold counterion on the overall chemochemical, regiochemical, and stereochemical outcome of the dearomatization of C2,3-disubstituted indoles with allenamides. , …”
mentioning
confidence: 94%
“…Tf ( were determined by single-crystal X-ray diffraction analysis. [22] We next turned to examine whether N-allenamides [23] (4) were applicable to the present reaction. We found that only trace amounts of the corresponding cyclization product 5a were detected under the above reaction conditions (see Scheme 3).…”
mentioning
confidence: 99%
“…Allenamides, also referred to as N -allenyl amides, are versatile synthetic building blocks in organic chemistry . In comparison to allenamines, which require careful preparation and handling due to their susceptibility toward hydrolysis and polymerization, allenamides exhibit enhanced stability due to delocalization of the nitrogen lone pair of electrons into the electron-withdrawing carbonyl.…”
mentioning
confidence: 99%